Associations between Language at 2 Years and Literacy Skills at 7 Years in Preterm Children Born at Very Early Gestational Age and/or with Very Low Birth Weight - Eveliina Joensuu; Petriina Munck; Sirkku Setänen; Jari Lipsanen; Mira Huhtala; Helena Lapinleimu; Suvi K. J. Stolt (MDPI AG, 2021)
Preterm children (born <37 gestational weeks) who are born at very early gestational age (<32 weeks, very preterm, VP) and/or with very low birth weight (≤1500 g, VLBW) are at increased risk for language and literacy deficits. The continuum between very early language development and literacy skills among these children is not clear. Our objective was to investigate the associations between language development at 2 years (corrected age) and literacy skills at 7 years in VP/VLBW children. Participants were 136 VP/VLBW children and 137 term controls (a 6-year regional population cohort, children living in Finnish-speaking families). At 2 years of corrected age, language (lexical development, utterance length) was assessed using the Finnish version of the MacArthur-Bates Communicative Development Inventory and the Expressive Language Scale from Bayley scales of Infant Development, second edition. At 7 years, children's literacy skills (pre-reading skills, reading, and writing) were evaluated. Statistically significant correlations were found in both groups between language development at 2 years and literacy skills at 7 years (r-values varied between 0.29 and 0.43, p < 0.01). In the VP/VLBW group, 33% to 74% of the children with early weak language development had weak literacy skills at 7 years relative to those with more advanced early language skills (11% to 44%, p < 0.001 to 0.047). Language development at 2 years explained 14% to 28% of the variance in literacy skills 5 years later. Language development at 2 years had fair predictive value for literacy skills at 7 years in the VP/VLBW group (area under the receiver operating characteristic (ROC) curve (AUC) values varied between 0.70 and 0.77, p < 0.001). Findings provide support for the continuum between very early language development and later language ability, in the domain of literacy skills in preterm children.